Trypanosoma cruzi antigen that interacts with the beta1-adrenergic receptor and modifies myocardial contractile activity - Joensen, Lilian G (2003)
Fil: Joensen, Lilian. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología; Argentina.